The Germination of Some Species Tropical Legume Seeds - Poetri, Eko; Marsetyo, Marsetyo (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2005)
A study to evaluate the seed germination of Leucaena pallida under climatic and soil conditions in Palu was conducted in village of Taipa, Sub district of North Palu, District of Palu. To compare with other species of legume trees however, this study involved Leucaena leucocephala cv Tarramba, Leucaena leucocephala cv Gumph and Gliricidia maculata. This experiment used completely randomized design with species of tropical tree legumes as treatment. Each treatment was replicated five times. Each experimental unit consisted of one tray (size 12.5 x 25 cm) and planted by 20 seed. Each tray was filled with soil while the seeds were planted one cm deep. All seeds were immersed in warm water (600C) for five minutes before planted. The base of the trays were drilled to create some holes for water to drain out. The trays were sprayed twice daily (07.00 am and 03.00 pm) to keep the soil to be moist using a very smooth sprayer. The variables recorded included the initiation time of germination, the range time of germination and the percentage of seed germination. The data obtained were analyses using the Minitab 11. Least significance difference was used to test for possible differences between treatment means. The result revealed that initiation time of germination and the range of germination were not varied (P>0.05) among the seeds tested. The initiation time of germination ranged between 9 to 12 d after sowing. Gliricidia maculata seed has the shortest period to germinate (12-16 d after sowing), meanwhile Leucaena leucocephala cv. Tarramba appear to be the longest (9-17 d after sowing). The highest seed viability was 60% in Leucaena leucocephala, cv Gump while the lowest was found in Gliricidia maculata (29%). In addition, both Leucaena pallida and Leucaena leucocephala cv Tarramba had medium seed germination (40% and 53% respectively). (Animal Production 7(3): 156-160 (2005)Key Words: Seed, Germination, Tropical Leguminous